Równanie Boltzmanna i Jego Znaczenie w Teorii Gazów - Zdzisław Szymański (Engineering Transactions, 1955)
Three ways of studying phenomena occurring in gases represented by phenomenological hydrodynamics, kinetic theory and statistical mechanics are discussed as well as the relations between them. Next, fundamental notions and assumptions of the kinetic theory of gases are represented on the basis of the so called kinetic distribution function. Boltz-mann's equation is derived in an elementary way and its mathematical and physical sense is discussed.